2008
DOI: 10.1063/1.2964757
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Formulations of Associating Polymers: Thermothinning versus Thermothickening.

Abstract: Articles you may be interested inShear-induced structure in polymer blends with viscoelastic asymmetry Abstract. Self-assembling and viscoelastic properties of thermothinning and thermothickening copolymers are described in semi-dilute aqueous solutions. Using grafted architectures derived from poly(sodium acrylate), we also investigate the possibilities to combine alkyl and LCST stickers, either grafted on different polymer chains or incorporated into the same macromolecule (double grafted copolymers), to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…In contrast, for the TVP polymer, high temperature becomes a favorable factor to enhance its viscosity buildup ability, which makes it possible to achieve oil and gas production in high-temperature reservoirs. Moreover, some studies (L'Alloret et al 1995;Hourdet et al 1998Hourdet et al , 2005Hourdet et al , 2008 also found the addition of salts could further enhance the hydrophobic interaction between those thermoresponsive grafts, contributing to the strengthening thermoviscosifying ability. The temperature and salt-induced thickening capability of TVPs could offer a fluid for oil and gas production in high-salinity and hightemperature reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, for the TVP polymer, high temperature becomes a favorable factor to enhance its viscosity buildup ability, which makes it possible to achieve oil and gas production in high-temperature reservoirs. Moreover, some studies (L'Alloret et al 1995;Hourdet et al 1998Hourdet et al , 2005Hourdet et al , 2008 also found the addition of salts could further enhance the hydrophobic interaction between those thermoresponsive grafts, contributing to the strengthening thermoviscosifying ability. The temperature and salt-induced thickening capability of TVPs could offer a fluid for oil and gas production in high-salinity and hightemperature reservoirs.…”
Section: Introductionmentioning
confidence: 99%